Implementasi Nilai-Nilai Islami dalam Pembelajaran Bahasa Arab pada Program Studi Non-Keislaman UIN Walisongo - Wati, Wiwit Rahma (Indonesian Journal of Islamic Education and Local Culture, 2025)
This study aims to examine the implementation of Islamic values in Arabic language learning within a non-Islamic study program at UIN Walisongo, The focus of the study is directed toward actual classroom practices rather than merely conceptual discussions. This research employs a qualitative field research design with a descriptive approach. The data sources include the Arabic language lecturer and students, collected through classroom observations, semi-structured interviews, and documentation of instructional materials such as the Semester Learning Plan (RPS), study program curriculum, and teaching materials. Data analysis was conducted through data reduction, thematic data presentation, and conclusion drawing. The findings indicate that the implementation of Islamic values in Arabic language learning occurs through four main domains. First, through learning materials that incorporate values of moral conduct (akhlak), proper manners (adab), and the habituation of religious practices within reading texts and dialogues. Second, through teaching methods and learning activities such as listening exercises, dialogues, group discussions, and presentations that foster diligence, cooperation, and self-confidence. Third, through lecturer–student interactions characterized by the lecturer’s role modeling in discipline, polite communication, prayer practices, and equitable treatment of students. Fourth, through learning evaluation that emphasizes academic honesty, fairness in assessment, and openness to constructive feedback.